Active gum karaya/Cloisite Na+ nanocomposite films containing cinnamaldehyde. (April 2019) - Cao, Thi Luyen; Song, Kyung Bin
Abstract: Gum karaya (GK) is an inexpensive and abundant source of polysaccharides in tropical countries. GK can be used for biodegradable film preparation without further extraction. In this study, active GK nanocomposite films containing Cloisite Na + (CLS) and cinnamaldehyde (CIN) were developed. The physical properties of the GK films were examined. The dispersion of GK (2.5%, w/v) and glycerol (55% of gum, w/w) exhibited film-forming capacity. Addition of CLS enhanced the physical properties of the films by the intercalation of GK molecules into the layered structure of CLS nanoparticles. This structure was elucidated in the X-ray diffraction pattern of the GK nanocomposite films. In particular, the tensile strength of the GK film containing 11% CLS was increased by 73%, compared to that of the GK film without CLS. Water solubility and water vapor permeability of the GK films were decreased with the addition of CLS. Moreover, the incorporation of 0.25%, 0.50%, and 0.75% CIN caused the increase in elongation at break of the GK film containing 11% CLS by 60%, 82%, and 43%, respectively. Furthermore, the addition of CLS and CIN increased the opacity of the GK films. The GK film containing 11% CLS and 0.75% CIN exhibited antimicrobial activities against the tested pathogens. Thus, the results in this study suggest that the GK/CLS nanocomposite films containing CIN can be applied as an active packaging material. Graphical abstract: Highlights: Gum karaya can be used as a novel material for biodegradable film preparation. Active gum karaya/Cloisite Na + films containing cinnamaldehyde were prepared. Physical properties of the nanocomposite films were improved. The nanocomposite films with cinnamaldehyde exhibited anitimicrobial activity.